The Political Outcomes of Housing Movements: Participatory Governance in Mass Housing Programmes - Valesca Lima (Critical Housing Analysis)
Research conducted over the past decade examining the impact of social movements on urban politics and housing policy has significantly enhanced our understanding of how these movements resist housing financialisation through direct action, social protest, and advocacy. However, further investigation is still required to comprehend the influence of housing movements on policy design and implementation, in order to understand the paths taken and how social movements shape housing and urban policies. This paper focuses on the self-management branch of the My House, My Life – Entities (Minha Casa, Minha Vida - Entidades), a mass housing programme in Brazil. The paper has two objectives. Firstly, it identifies the strategies that nationally organised urban and housing movements employ to advocate for the inclusion of housing self-management in federal mass housing programmes. Secondly, it examines the policy implications of implementing a participatory governance model (co-management) in national housing programmes, with an emphasis on policy lessons learned. To accomplish this, policy documents, housing movement reports, and news media items were utilised to systematically trace the trajectory to success and examine the policy lessons for participatory governance. This paper makes two contributions: it enriches the literature on social movements against housing financialisation by analysing citizen participation in housing policy design and implementation and it contributes to the field of research on the consequences of social movements by examining the influence of social movements in shaping and housing policies.